독립형 액화가스 저장탱크의 BOG 발생에 대한 실험적 분석 - 차승주(Seung-Joo Cha); 배진호(Jin-Ho Bae); 이동하(Dong-Ha Lee); 김태욱(Tae-Wook Kim); 김슬기(Seul-Kee Kim); 이제명(Jae-Myung Lee) (Han-guk haeyang gonghak hoeji (Online), 2018)
With the tightening of environmental regulations (i.e., IMO Tier III), natural gas (NG) has been spotlighted as an eco-friendly fuel with few air pollutants other than nitrogen oxides (NOx) and sulfur oxides (SOx). For reasons of economic efficiency, it is mainly stored and transported in a liquid state at $-163^{°}C$, which is a cryogenic temperature, using a liquefied gas storage tank. Accordingly, it is necessary to reduce the boil-off gas (BOG) occurrence due to the heat flow according to the temperature difference between the inside and outside of the storage tank. Therefore, in this study, a BOG measurement test on an independent-type storage tank made up of SUS304L was carried out. The test results showed the tendency for BOG occurrence according to the temperature under different filling ratios.